Menu item prices and promotions offered on a meal delivery app in the UK and their socio-economic patterns - Yuru Huang; Nuwan Weerasinghe; Jean Adams; Holly Rippin; Kathrin Hetz; Olga Zhiteneva; Kremlin Wickramasinghe (Public Health Nutrition)
Abstract